পরিবেশ : রাজনৈতিক দলের ভূমিকা - ফারূক, মোহিউদ্দিন; আহমদ, মেসবাহ; কবির, ইকবাল
On environment in Bangladesh and role of political parties; papers read at a opinion meeting organized by Bāṃlādeśa Paribeśa Āinabida Samiti, Dhaka.